PERAN GURU DALAM OPTIMALISASI PENDIDIKAN MORAL SISWA PADA MATA PELAJARAN IPS - Nasrin Syafika; Alfin Mustikawan (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The negative impact of globalization is that it makes people influence each other's thoughts and behavior because of the ease of communication technology. This is felt by students who begin to forget moral values, so that it has an impact on education, including in schools, it is necessary for the teacher's role in optimizing students' moral education in social studies subjects that are rich in attitudes, values, morals, ethics and behavior. The purpose of this study was to determine: The role of the teacher in optimizing the moral education of students in grades 9A and 9B in social studies subjects, the supporting and inhibiting factors of social studies teachers in optimizing the moral education of students in grades 9A and 9B and optimizing the role of social studies teachers in the formation of moral education for students in grades 9A and 9B. The research was conducted at MTs Islamiyah Sukopuro using observations, interviews, documentation with social studies teachers, homeroom teachers, students and parents. Data analysis includes data collection, data condensation, data presentation and conclusion drawing. The results showed that: The teacher's role in optimizing students' moral education was more optimal in grade 9B by using the teacher's exemplary method and good habits, carrying out activities or special treatment (punishment and reward) as well as providing motivation and using learning methods adapted to social life. student. The supporting factors for teachers in optimizing students' moral education are the students' religious provisions from an early age and the good habits of parents, while the inhibiting factors are the lack of attention and monitoring of parents and the students' indifference when warned by the teacher. Abstrak Dampak negatif globalisasi yaitu menjadikan seseorang saling mempengaruhi pemikiran dan perilaku karena mudahnya teknologi komunikasi. Hal tersebut dirasakan siswa yang mulai melupakan nilai-nilai moralitas, sehingga berdampak pada pendidikan termasuk di sekolah, maka diperlukan peran guru dalam optimalisasi pendidikan moral siswa pada mata pelajaran IPS yang kaya akan sikap, nilai, moral, etika dan perilaku. Tujuan penelitian ini untuk mengetahui: Peran guru dalam optimalisasi pendidikan moral siswa kelas 9A dan 9B pada mata pelajaran IPS, faktor pendukung dan penghambat guru IPS dalam optimalisasi pendidikan moral siswa kelas 9A dan 9B serta optimalisasi peran guru IPS dalam pembentukan pendidikan moral siswa kelas 9A dan 9B. Penelitian dilakukan di MTs Islamiyah Sukopuro menggunakan observasi, wawancara, dokumentasi dengan guru IPS, wali kelas, siswa dan orang tua. Analisis data meliputi pengumpulan data, kondensasi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: Peran guru dalam optimalisasi pendidikan moral siswa lebih optimal di kelas 9B dengan menggunakan metode keteladanan guru dan pembiasaan-pembiasaan baik, melakukan aktivitas atau perlakuan khusus (punishment dan reward) serta memberikan motivasi dan menggunakan metode pembelajaran yang disesuaikan dengan kehidupan sosial siswa. Faktor pendukung guru dalam optimalisasi pendidikan moral siswa yaitu bekal agama siswa sejak dini dan kebiasaan baik orang tua siswa, sedangkan faktor penghambatnya adalah kurangnya perhatian dan pantauan orang tua serta adanya sikap acuh siswa ketika diperingatkan oleh guru.